ANALYSIS OF THE IMPLEMENTATION OF VILLAGE FINANCIAL MANAGEMENT ACCORDING TO THE MINISTER OF HOME REGULATION NO. 20 OF 2018 (Case Study: Pesarean Village, Adiwerna District, Tegal District) - Nurul Mahmudah; Yusri Anis Faidah (Jurnal Scientia, 2023)
The purpose of writing is to determine how to implement village financial management according to Minister of Home Affairs Regulation No. 20 of 2018 (Case Study: Pesarean Village, Adiwerna District, Tegal Regency). Data collection used was direct observation and interviews with the Village Head, Village Secretary, Village Treasurer and BPD. The method used in this research is a descriptive qualitative method, with data sources obtained from secondary data by conducting observations in Pesarean village, Adiwerna subdistrict, Tegal district. The research results show that overall, the implementation of village financial management in Pesarean Village is by PERMENDAGRI No. 20 of 2018, which consists of planning, implementation, administration, reporting and accountability. The Pasadena Village Government, in its implementation in addition to complying with PERMENDAGRI No. 20 of 2018, has also digitized the implementation of village financial management, namely through the SISKEUDES application, which makes it easier for village governments to compile village finances. However, several regulations still need to be implemented, namely in the planning and reporting process. In the planning process, namely in article 32, paragraph 3. Along with the policy output of the Pesarean Village Regent's Regulation regarding the Draft Village Regulation on APB Des, it was mutually agreed upon in February. This caused a delay in preparing the APBDes draft. Even though it is known in the regulations that the Draft Village Regulations regarding the Village APB, as referred to in paragraph (2), are mutually agreed upon by October of the current year. The regulations in Article 38, Paragraph 2 concerning Village Regulations regarding Village APB, as referred to in paragraph (1), are stipulated by December 31 of the previous fiscal year. However, in Pesarean Village, there was a delay in enacting Village Regulations due to the policy output that came into effect in February. There are reporting processes not by PERMENDAGRI No. 20 of 2018, namely in article 69, where the Pasadena Village, in submitting the report, experienced a delay in submitting the final report in December. In contrast, according to the regulations, the Regent/Mayor submitted a consolidated report on the implementation of the Village APB to the Minister through the Director General of Village Government Development by the second week of August 2018.